Stress management intervention program for teaching staff at~private engineering colleges in~Tamil Nadu to improve their job~performance and well-being - R. Dhaneesh; V. S. Iswarya (Rajagiri Management Journal (RAMJ), 2023)
Purpose - Stress at workplace is quite common in all sorts of environment. It can be occurring when the demand in the job does not match with the requirements; thereby, it affects their performance. The study was conducted with the aim to identify the major factors that induce stress for teaching professionals in private engineering colleges and its impact towards job performance. From the observation and discussion, it was found that Workload, Working Hour, Salary, Role Ambiguity and Lack of Social Support are the major factors for stress. Design/methodology/approach - A structured questionnaire was framed with the help of stress-causing factors and their effect on job performance. In addition to this, a few questions were asked related to stress management intervention program. The survey was conducted with 370 respondents, while further analysis was carried out with the filled 260 respondent's data using descriptive statistics, correlation, regression, ANOVA and SEM. Findings - The study reveals that workload plays a significant role in stress whereas other factors are consequently lower than that. Also, the primary-level intervention programs are more effective than secondary-level intervention programs to reduce the stress level of stressors. Originality/value - The paper was originally done by collecting data from the staff.
Keywords: 650; Intervention programs; Role ambiguity; Salary; Social support; Workload